Agency Banking and Financial Inclusion in Mukono Municipality: A Case Study of Stanbic Bank Uganda Mukono Branch - Carolyn Tusiime (Uganda Christian University, 2024)
Examining how agency banking affects financial inclusion at Stanbic Bank Mukono was the aim of the study. To be more precise, the study assessed how the number of banking agents employed at Stanbic Bank Mukono, agent transaction volumes, and geographic coverage affected the bank's efforts to promote financial inclusion. The conceptualization of the study was guided by the agency theory. Primary data was gathered by the use of questionnaires and interview guides in a cross-sectional survey methodology. Quantitative data was gathered from 17 respondents, or 100% of the target population of 20 respondents, which comprised bank agents, managers, supervisors, and employees. Quantitative data was gathered using simple random sampling, and qualitative data was obtained through purposive sampling from a sample of two interviews with a 100% response rate. Descriptive statistics were employed in the study to characterize the pertinent features of the phenomena. The study's conclusions showed that extending geographic reach by establishing more financial institutions or mobile banking services greatly improves accessibility for people living in isolated or underserved parts of Mukono. This improved accessibility contributes to closing the gap in financial services between rural and urban areas. Expanded geographic reach is correlated with increased local community growth and economic activity. More people having access to financial services makes them more capable of participating in economic activities like investing, saving, and borrowing. As more individuals gain access to financial services, they are better equipped to engage in economic activities such as saving, investing, and accessing credit, which stimulates local economies. The study recommended that the bank administration should continue to expand the network of financial institutions and agents in undeserved and remote areas of Mukono. Conduct regular surveys and feedback sessions with residents and financial service providers. Use evaluation findings to refine strategies and address any emerging issues or gaps in service. Future studies need to be conducted on Effectiveness of Financial Literacy Programs Associated with Agency Banking.